Bonding Lithium Metal with Garnet Electrolyte by Interfacial Lithiophobicity/Lithiophilicity Transition Mechanism over 380 °C. Issue 4 (17th February 2023) - Jin, Yang; Lu, Hongfei; Lyu, Nawei; Jiang, Xin; Zhang, Di; Zhang, Zili; Xu, Jing; Sun, Bin; Liu, Kai; Wu, Hui
Abstract: Garnet electrolytes, possessing high ionic conductivity (10 −4 –10 −3 S cm −1 at room temperature) and excellent chemical/electrochemical compatibility with lithium metal, are expected to be used in solid‐state lithium metal batteries. However, the poor solid–solid interfacial contact between lithium and garnet leads to high interfacial resistance, reducing the battery power capability and cyclability. Garnet electrolytes are commonly believed to be intrinsically lithiophilic, and lithiophobic Li2 CO3 on the garnet surface accounted for the poor interfacial contact. Here, it is proposed that the interfacial lithiophobicity/lithiophilicity of garnets (LLZO, LLZTO) can be transformed above a temperature of ≈380 °C. This transition mechanism is also suitable for other materials such as Li2 CO3, Li2 O, stainless steel, and Al2 O3 . By using this transition mechanism, uniform and even lithium can be strongly bonded no‐surface‐treated garnet electrolytes with various shapes. The Li–LLZTO interfacial resistance can be reduced to ≈3.6 Ω cm 2 and sustainably withstood lithium extraction and insertion for up to 2000 h at 100 µA cm −2 . This high‐temperature lithiophobicity/lithiophilicity transition mechanism can help improve the understanding of lithium–garnet interfaces and build practical lithium–garnet solid–solid interfaces. Abstract : This work reports a simple method for enhancing the solid–solid contact between garnet electrolytes (LLZTO, LLZO) and lithium metal and elucidates the lithiophobicity/lithiophilicity transition mechanism of garnets and various substrates (Li2 O, Li2 CO3, Al2 O3 ) affected by molten lithium temperature, which can improve their awareness of lithium–garnet interfaces and help to build practical interfaces for solid‐state lithium metal batteries.